Penerapan Demokrasi Pendidikan: Kepemimpinan Guru dalam Membentuk Karakter Siswa - Shella Satiwi Guci; Firman Firman; Riska Ahmad (Universitas Islam Sumatera Utara, 2022)
Education is the need of every individual. In education there is always progress in a better direction, such as the realization of educational democracy in learning, which includes the idea of giving students freedom to express opinions, surrender and equal opportunities without differences in ethnicity, race or class. This study uses the literature review method, where information is obtained from journals, articles, and websites on the internet, and is analyzed with a qualitative approach using data analysis techniques in the steps of information retrieval, data reduction, data presentation, and inference. The results of the study show that students are currently not only used as learning objects, but also as interlocutors in the learning process. Therefore, it is hoped that teachers will succeed in creating a democratic learning environment for students in such a way that the character of students is formed.